Effect of dehydroepiandrosterone add‐on therapy on mood, decision making and subsequent relapse of polydrug users. (26th March 2015) - Ohana, David; Maayan, Rachel; Delayahu, Yael; Roska, Paola; Ponizovsky, Alexander M.; Weizman, Abraham; Yadid, Gal; Yechiam, Eldad
Abstract: A major problem in the treatment of addiction is predicting and preventing relapse following a rehabilitation program. Recently, in preclinical rodent studies dehydroepiandrosterone (DHEA) was found to markedly improve the resistance to drug reuse. In a double‐blind, placebo‐controlled study, we examined the effect of DHEA on relapse rates in adult polydrug users taking part in a detoxification program enriched with intensive psychosocial interventions and aftercare. During treatment, participants (79 percent males, mean age 28) consumed DHEA (100 mg/day) or placebo daily for at least 30 days. Of the 121 initial volunteers, 64 participated for at least 1 month. While in treatment, DHEA reduced negative affect on the Positive and Negative Affect Scale ( F  = 4.25, P  = 0.04). Furthermore, in a 16‐month follow‐up, we found that reuse rates in the DHEA condition were about a third compared with placebo (12 versus 38 percent; χ 2  = 5.03, P  = 0.02). DHEA treatment also resulted in an increase in DHEA sulfate (DHEA‐S) 1 month following treatment, and the level of DHEA‐S predicted relapse in the follow‐up assessment. Abstract : We examined the effect of dehydroepiandrosterone (DHEA) on relapse to drug usage in adult poly‐drug users taking part in a detoxification program. Top pane: In a 16 months follow‐up, we found that re‐use rates in the DHEA condition were about a third compared to placebo (12% versus 38%). Bottom pane : Compared to their counter‐parts, individuals who re‐used drugs, had lower levels of DHEA‐S following 1 month of treatment (t(34) = 2.34, p =.03). Error terms denote standard errors.